Resolusi syariah oleh majlis penasihat shariah Bank Negara Malaysia: tinjauan perspektif undang-undang - Hussain, Mohammad Azam; Hassan, Rusni; Hasan, Aznan (Dewan Bahasa dan Pustaka, 2013)
The Shariah Advisory Council of Bank Negara Malaysia is the highest bodyestablished under the law and has the authority to ascertain Islamic law in Shariah matters relating to Islamic finance in Malaysia. The Shariah rulings made by the Syariah Advisory Council are in the form of Shariah resolutions which was first issued dated 8th July 1997. Shariah Resolutions are essential as guidance to Islamic financial stakeholders, particularly banking and financial institutions in offering Islamic financial business, Shariah committees as well as society. In addition, these resolutions are important as a reference to the court and arbitrators in deciding cases relating to Islamic finance in Malaysia. This paper discusses Shariah resolutions issued by the Shariah Advisory Council from the legal perspective as stipulated in the existing law in regulating the Islamic financial system in Malaysia. Further, this paper also analyzes the legal issues arising with respect to the Shariah resolutions issued by the Shariah Advisory Council